Hubungan Kondisi Sanitasi Lingkungan dengan Keberadaan Jentik Aedes Aegypti diwilayah Kerja Puskesmas Sako Palembang - Zairinayati; MIfta Oktarisa (IKesT Muhammadiyah Palembang, 2023)
Environmental sanitation is an effort to control environmental factors which are links in the chain of disease transmission. The purpose of this study was to determine the density of Aedes Aegypti mosquito larvae, to describe environmental sanitation including trash cans, clean water reservoirs, and the frequency of draining bathtubs. This research method uses a descriptive analytical and cross sectional design and uses a sample of 73 respondents. This research was conducted in the working area of ​​the Sako Palembang Health Center on April 28-May 12 2022. The results of this study concluded that based on statistical tests with the chi-square test, the p value was obtained (0.000 > 0.05) so there was a relationship between trash cans and the presence of larvae. Aedes aegypti. P value (0.014 > 0.05) means there is a relationship between clean water reservoirs and the presence of Aedes Aegypti larvae. P value (0.000 > 0.05) means there is a relationship between draining the bath and the presence of Aedes Aegypti larvae. It is recommended that the community pay more attention to cleaning water reservoirs, improve disposal systems and waste management, and pay attention to the condition of the home environment so that it is always neat and clean.